Cognitive Functioning in Schizophrenia: Leveraging the RDoC Framework - Barch, Deanna M.; Young, Jared W. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book highlights recent research investigating psychological and neural mechanisms contributing to dysfunctional cognition in people with schizophrenia. The work on cognition in schizophrenia from the past 20 years is highlighted, and emphasis throughout the book is placed on utilizing the Research Domain Criterion framework. Thus, the book also covers animals work relevant to schizophrenia that assesses behaviors utilizing the same framework, enabling mechanistic studies and highlighting potential biomarkers of function. The book also includes important areas of research in the field of cognitive function in schizophrenia that have received less attention, such as cognitive side-effects of current treatments and olfactory-based cognition. Altogether, the book provides a translational perspective of the most-up-to-date research on cognition in schizophrenia to-date, but with identification of novel directions for research initiatives.
MATRICS - an update -- Cognitive [Computational] Neuroscience Test Reliability and Clinical Applications for Serious mental illness (CNTRaCS) Consortium: Progress and Future Directions -- Attention in Schizophrenia -- Perceptual Functioning -- Episodic Memory and Schizophrenia: From Characterization of Relational Memory Impairments to Neuroimaging Biomarkers -- Working Memory in People with Schizophrenia -- "Targeting Frontal Gamma Activity with Neurofeedback to Improve Working Memory in Schizophrenia" -- Cognitive Dysfunction as a Risk Factor for Psychosis -- Environmental Risk Factors and Cognitive Outcomes in Psychosis: Pre-, Perinatal, and Early Life Adversity -- Developmental manipulation-induced changes in cognitive functioning -- Genetic underpinnings of cognitive dysfunction in schizophrenia -- Primate models of cognitive deficit re schizophrenia -- Olfactory cognitive deficits -- Medication/Anticholinergic burden impacting cognition in schizophrenia An Update on Treatment of Cognitive Impairment Associated with Schizophrenia -- Cannabis & cognition -- Sex/gender differences -- Neuroinflammation linked to cognition.
Keywords: Medicine -- Research; Biology -- Research; Medical sciences; Drug development; Pharmacology; Genetics -- Research; Clinical medicine -- Research; Biochemical markers; Translational Research; Preclinical Research; Pharmacology; Genetics Research; Clinical Research; Biomarkers